A thousand total colonoscopies: what is the relationship between distal and proximal findings?. - Sousa Andrade, Carla (2008)
Flexible sigmoidoscopy is indicated for colorectal cancer screening. The decision about who needs total colonoscopy based on distal findings is still controversial because of the uncertainty of the associations between distal and proximal findings.The purpose of the study was to characterize distal findings in patients with total colonoscopy, to investigate its importance as markers of advanced proximal lesions and to evaluate the usefulness of a clinical Predictive Index, already published in the literature, in the identification of these lesions.Retrospective analysis of the patients submitted to total colonoscopy between January 2006 and February 2007, with selection of 1000 consecutive cases with reference to polyps. We analysed demographic data, indication for the exam and morphological and histological characteristics of the polyps. Advanced lesion was defined as any adenoma larger than 10 mm or any polyp with villous characteristics, high grade dysplasia or cancer. The Predictive Index was obtained through the assignment of points to 3 categories: sex, age and distal findings, which result in 3 groups: low, intermediate and high risk.The mean age of patients was 64,69 years and 65,1% were male. Distal and proximal polyps were identified in 829 (82,9%) and 369 (36,9%) patients, respectively. Advanced distal lesion was found in 342 patients (34,2%) and advanced proximal lesion in 98 (9,8%). 587 patients (58,7%) were in the high risk group. In the group of patients with advanced proximal lesion, a third presented low and intermediate risk, 52% had no distal polyps, 88,7% had less than three distal polyps and 71,4% had no advanced distal lesion. Sensitivity values for these four categories ranged between 11,2% and 66,6%.If the decision to perform total colonoscopy is based on distal colonic findings or on the Predictive Index, the ability to identify advanced proximal lesion is markedly reduced, endangering the aim of a screening program.